Pyroptosis by caspase11/4‐gasdermin‐D pathway in alcoholic hepatitis in mice and patients - Khanova, Elena; Wu, Raymond; Wang, Wen; Yan, Rui; Chen, Yibu; French, Samuel W.; Llorente, Cristina; Pan, Stephanie Q.; Yang, Qihong; Li, Yuchang; Lazaro, Raul; Ansong, Charles; et al. (Hepatology (Baltimore, Md.), 2018)
Alcoholic hepatitis (AH) continues to be a disease with high mortality and no efficacious medical treatment. Although severe AH is presented as acute on chronic liver failure, what underlies this transition from chronic alcoholic steatohepatitis (ASH) to AH is largely unknown. To address this question, unbiased RNA sequencing and proteomic analyses were performed on livers of the recently developed AH mouse model, which exhibits the shift to AH from chronic ASH upon weekly alcohol binge, and these results are compared to gene expression profiling data from AH patients. This cross‐analysis has identified Casp11 (CASP4 in humans) as a commonly up‐regulated gene known to be involved in the noncanonical inflammasome pathway. Immunoblotting confirms CASP11/4 activation in AH mice and patients, but not in chronic ASH mice and healthy human livers. Gasdermin‐D (GSDMD), which induces pyroptosis (lytic cell death caused by bacterial infection) downstream of CASP11/4 activation, is also activated in AH livers in mice and patients. CASP11 deficiency reduces GSDMD activation, bacterial load in the liver, and severity of AH in the mouse model. Conversely, the deficiency of interleukin‐18, the key antimicrobial cytokine, aggravates hepatic bacterial load, GSDMD activation, and AH. Furthermore, hepatocyte‐specific expression of constitutively active GSDMD worsens hepatocellular lytic death and polymorphonuclear leukocyte inflammation. Conclusion: These results implicate pyroptosis induced by the CASP11/4‐GSDMD pathway in the pathogenesis of AH. (Hepatology 2018;67:1737‐1753).